Pola Komunikasi Keagamaan Masyarakat Muslim di Ruang Digital - Baidawi (Mediakita, 2022)
The Covid-19 pandemic has colored the phenomenon of shifting patterns of religious communication among Muslim communities in cyberspace which is considered more efficient, interactive and varied. Some religious activities that are commonly found include online tahlilan, scientific studies, Islamic motivational seminars, khataman and the Qur'an via WhatsApp Group. Religious activities are usually carried out face-to-face and are accommodated in a taklim assembly or holy place, but since the emergence of the pandemic, many religious rituals are spent through virtual space. Religious activities carried out by the Muslim community through cyberspace have actually widened the distance between entities. Because there is no face-to-face meeting (physical), one's expressions, non-verbal messages and emotions are not represented, because they only rely on a touch of the screen (face to screen). While this research method is descriptive qualitative with virtual ethnographic research type. The results of the research findings are that the phenomenon of religious activity in virtual space can slowly reduce the value of sacredness, solemnity, and even blessing in carrying out religious rituals. In addition, the shift in religious communication is not only limited as a communication tool, but has expanded as a construction of Muslim community identity and an arena for meeting religious symbols. Entities can simultaneously produce messages to audiences, and at the same time, entities can produce content that is sometimes unclear to whom. Key Word : Communication Shift, Muslim Society, Covid-19 Pandemic